Analysis of physical condition of karate athletes - Ade Ikamala Mustofa; Sahri Sahri (Sriwijaya Journal of Sport, 2022)
Physical conditions affect athletes during training and during matches. Therefore, the following study aims to analyze the physical condition of the karate athletes Inkanas Dojo Yondan, Central Lampung Regency. This research is descriptive quantitative research. The research instrument used was 6 test items, namely 60 second push-ups, 30m sprint run, shuttle run, standing board jump, MFT, and V-sit and reach. The sample of this research is the 10 athletes of Karate Inkanas Dojo Yondan Central Lampung. This research uses purposive sampling technique. The results showed that there were 8 athletes (80%) in the very poor category, 0 athletes (0%) in the poor category, 2 athletes (20%) in the sufficient category, 0 athletes (0%) in the good category, and 0 athletes (0%) in the excellent category. From the data above, the highest frequency is in the very poor category, namely 8 athletes (80%). So, it can be concluded that the physical condition of the karate athlete Inkanas Dojo Yondan is very poor. This research can be used as a reference as an appropriate training program focused on the elements of physical condition in the sport of karate.